Peran didikan subuh dalam membentuk karakter religius dan kedisiplinan ibadah pada anak di era teknologi - Aswati, Fajar; Jarir, Jarir; Sufia, Neng; Febriyani, Safna (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2024)
Subuh Education is a form of religious education that is carried out intensively at dawn. This activity is important in forming religious character and discipline in worship in children, especially in the challenging era of technology. This study aims to build children's religious character and discipline in worship as a foundation for noble personality. The digital era presents challenges, such as uncontrolled access to content, the influence of global culture, and dependence on technology that reduces awareness of worship. The study explores the role of Subuh Education and adaptive strategies to overcome these challenges. This study uses a library research method with observation and documentation data collection techniques. The results of the study show that Subuh Education plays a significant role in forming children's religious character and discipline in worship, such as praying on time and routinely reading the Qur'an. However, the influence of technology can be an obstacle if its use is not regulated wisely. This study concludes that Subuh Education is an effective strategy for building children's religious character and discipline in worship in the digital era.